A Study of The Brief Multidimensional Students' life Satisfaction Scale (BMSLSS) with Syrian Secondary and University Students - Emtanuos Michaeel (Sultan Qaboos University, 2010)
The Brief Multidimensional Students' Life Satisfaction Scale (BMSLSS) is a self-report measure developed to assess life satisfaction among students in five specific domains: family, friends, school, self, and daily life. The purpose of the current study was to develop an Arabic version of this measure and to investigate its psychometric properties with Syrian secondary students as well as university students. With a sample of (N=1604), several methods were used to estimate the reliability and validity of the measure. The results showed satisfactory test-retest reliability and internal consistency coefficients. Also, the results provided evidence for the convergent and divergent validity. Further evidence for the construct validity of the instrument was provided by studying the inter-correlations of its five subscales as well as the correlations of these subscales with the subscales of the entire instrument. At the same time, validity was supported by the correlations of the five subscales with achievement. In sum, the findings of this study show that the psychometric properties obtained from administering the instrument to a sample of secondary school and university students meets acceptable levels. Recommendations were made to conduct further psychometric studies upon the Arabic version of BMSLSS and to administer this version in cross- cultural studies.